Actions Speak Louder Than Words? The Untapped Potential of V4 Parliaments in EU Affairs. Issue 3 (August 2022) - Borońska-Hryniewiecka, Karolina; Grinc, Jan
This article offers the first ever comparative analysis of the involvement of V4 parliaments in the sphere of European Union (EU) affairs. Its underlying research objective is to determine what conditions V4's parliamentary participation in various EU-oriented activities such as domestic scrutiny of the government's EU policy, the political dialogue with the Commission, the Early Warning System for subsidiarity control, and the green card initiative. Based on the actual scrutiny output, parliamentary minutes, and data from questionnaires, we address the questions: (1) To what extent domestic legislatures act as autonomous as opposed to government-supporting actors in these arenas? (2) Do they mostly act as EU veto players, or try to contribute constructively to the EU policy-making process by bringing alternative policy ideas? (3) What are their motivations for engaging in direct dialogue with EU institutions in addition to domestic scrutiny? and (4) How MPs envisage their own EU-oriented roles? While the article reveals that V4 parliaments mostly act as gatekeepers in the sphere of EU affairs, it also casts a new light on the previous literature findings related to the EU-oriented performance of the Czech and Polish lower chambers. We conclude that, generally, V4 parliaments refrain from fully exploiting their relatively strong formal prerogatives in EU affairs—a fact that can be partly explained by the composition of their ruling majorities.